1997
DOI: 10.1074/jbc.272.12.7846
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Exchanges of Polar Amino Acids in the Transmembrane Domains of a Platelet-activating Factor Receptor Generate Both Constitutively Active and Inactive Mutants

Abstract: To determine ligand-binding sites of a platelet-activating factor (PAF) receptor, alanine-scanning mutagenesis was carried out. All 23 polar amino acids in the putative 7-transmembrane (TM) domains of a guinea pig PAF receptor were individually replaced with alanine. The ligand-binding properties of mutant receptors were determined after transient expression in COS-7 cells. Mutants in TM II (N58A, D63A), TM III (N100A, T101A, S104A) and TM VII (D289A) displayed higher PAF-binding affinities than seen with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 48 publications
4
29
0
2
Order By: Relevance
“…This indicates that Asn-137 participates in maintaining the ground state of receptor activity. Our results are in concert with previous studies showing that mutation of Asn (relative position 3.35) in G␣ q /G␣ i -coupled GPCRs such as the platelet-activating factor (PAF) receptor, the bradykinin B2 receptor, and the AT1 angiotensin II receptor induces constitutive activity (26,27).…”
Section: Fig 2 Phylogenetic Diversity Of Gpr34 In Fishsupporting
confidence: 78%
“…This indicates that Asn-137 participates in maintaining the ground state of receptor activity. Our results are in concert with previous studies showing that mutation of Asn (relative position 3.35) in G␣ q /G␣ i -coupled GPCRs such as the platelet-activating factor (PAF) receptor, the bradykinin B2 receptor, and the AT1 angiotensin II receptor induces constitutive activity (26,27).…”
Section: Fig 2 Phylogenetic Diversity Of Gpr34 In Fishsupporting
confidence: 78%
“…Using the cloned PAFR and its mutants expressed in Chinese hamster ovary cells, we showed that activation of PAFR leads to inhibition of adenylate cyclase, elevation of intracellular calcium concentration, arachidonic acid liberation, and mitogen-activated protein kinase activation. These intracellular effectors differed in their sensitivities to pertussis toxin (PTX) treatment (16,21).…”
mentioning
confidence: 99%
“…In the tammar, the transmembrane domains had the highest conservation with eutherians and these were also highly conserved among all marsupial species. Based on mutation studies, transmembrane domains 5, 6 and 7 are predicted to be involved in Paf binding and, in particular, three histidine residues are thought to constitute the three-dimensional Paf-binding pocket and were completely conserved in the tammar (Ishii et al 1997). Other regions important for PTAFR function that were conserved in the tammar include the third intracellular loop, which is required for intracellular signalling, and the C-terminal domain, which is phosphorylated before desensitisation of the receptor (Prescott et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The tammar PTAFR gene was highly conserved with that of PTAFR in eutherian species. Furthermore, the seven transmembrane domains were all highly conserved between tammar and all species examined, and this included conservation of the putative Paf-binding pocket (Ishii et al 1997, Prescott et al 2000. These domains are characteristic of a member of the G proteincoupled receptor superfamily and, together with conservation of the regions involved in translation of PTAFR signalling and desensitisation (Ishii & Shimizu 2000, Prescott et al 2000, suggest that the functional role of PTAFR has been conserved in the tammar.…”
Section: Discussionmentioning
confidence: 99%